Impact of Water Pollution on Waterborne Infections: Emphasizing Microbial Contamination and Associated Health Hazards in Humans - Nazish Mazhar Ali; Muhammad Kamran Khan; Bushra Mazhar; Madiha Mustafa (Discover Water)
Abstract Water pollution is a major global issue due to the entrance of hazardous waste from industrial, agricultural, and urban activities. Several environmental elements, including precipitation, climate, and soil quality, contribute to this problem, which has serious ramifications for human health. Contaminated water is a major cause of waterborne infections, especially in underdeveloped nations where poor sanitation and water management worsen the problem. Every year, millions of people suffer from gastrointestinal infections and other disorders caused by microbial pollutants such bacteria (Escherichia coli, Vibrio cholerae, Salmonella spp.), viruses, and protozoa (Giardia lamblia, Cryptosporidium parvum). Despite advances in water treatment and sanitation in developed countries, outbreaks continue in places with little resources. Industrial pollution, agricultural runoff, and untreated sewage are common sources of pathogenic microorganisms, which harm both surface and groundwater. This review investigates the causes of water pollution, the many types of pollutants (biodegradable, non-biodegradable, and persistent organic pollutants), and the effects on human health. It emphasizes the presence of bacterial pathogens such as Legionella spp., Pseudomonas aeruginosa, and Campylobacter jejuni, as well as protozoan and viral agents that cause serious illnesses. The assessment emphasizes the importance of better water management, stricter pollution regulations, and the development of innovative treatment technologies to reduce waterborne diseases. Addressing these concerns is critical for protecting public health, especially in areas prone to water scarcity and microbiological pollution.